2018
DOI: 10.7181/acfs.2018.02019
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the orbicularis oculi myocutaneous flap in periorbital reconstruction

Abstract: BackgroundThe esthetic and functional outcomes of periorbital defect reconstruction are very important because of the complex anatomy and specialized functions of this region. The orbicularis oculi myocutaneous (OOMC) flap is useful for the reconstruction of periorbital defects. But, according to the location and depth of the defects, the reconstruction using OMC flaps with various techniques is rare. The authors have used various kinds of OOMC flaps in various situations and we present an analysis of our expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The skin of the medial canthus is thicker than the upper and lower eyelids but thinner than the nose and the glabella. 19 There are other complex parts in the medial canthal region, notably the medial canthal ligament and the lacrimal duct, with depression in the middle. Reconstruction of the medial cantal area must consider several factors, such as maintaining the aesthetics and contours of each subunit in the nasal wall and eye area and avoiding distortion of the surrounding structural areas such as the ala nasi and eyelids.…”
Section: Discussionmentioning
confidence: 99%
“…The skin of the medial canthus is thicker than the upper and lower eyelids but thinner than the nose and the glabella. 19 There are other complex parts in the medial canthal region, notably the medial canthal ligament and the lacrimal duct, with depression in the middle. Reconstruction of the medial cantal area must consider several factors, such as maintaining the aesthetics and contours of each subunit in the nasal wall and eye area and avoiding distortion of the surrounding structural areas such as the ala nasi and eyelids.…”
Section: Discussionmentioning
confidence: 99%
“…The OOM is a circular muscle that supports both the upper and lower eyelids surrounding the palpebral fissure and is usually divided into 3 parts: pretarsal, preseptal, and orbital 6. In 1991, Yoshimura et al reported the use of the temporal flap with an OOM pedicle for repairing upper-eyelid defects 7.…”
Section: Discussionmentioning
confidence: 99%
“…The OOM is a circular muscle that supports both the upper and lower eyelids surrounding the palpebral fissure and is usually divided into 3 parts: pretarsal, preseptal, and orbital. 6 In 1991, Yoshimura et al reported the use of the temporal flap with an OOM pedicle for repairing upper-eyelid defects. 7 In 1998, Zhou et al studied the anatomy of the OOM and eyelid by cadaver research and concluded that the blood supply of the OOM is very abundant: the chief vessel origins come from the superficial temporal vessel, lacrimal artery, and transverse facial laterally, the supraorbital vessel, supratrochlear vessel, dorsal nasal artery, medial palpebral artery, and angular artery centrally.…”
Section: Discussionmentioning
confidence: 99%
“…Autogenous orbicularis oculi muscle flap grafts have been described as important role in eyelid repair and reconstruction, like the management of eyelid diseases: ectropion, lagophthalmos, full-thickness eyelid defects. [11][12][13] The orbicularis oculi muscle is distributed around the palpebral fissure, which makes it easy to transfer the flap pedicled with it to the adjacent area of defect, in addition, its rich blood supply ensures the survival of flap and motility.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Studies have reported the use of orbicularis oculi muscle flap for eyelid reconstruction. 11,12 This article reports the technique of the supra-brow island flap pedicled with the orbicularis oculi muscle for management of orbital implant exposure with a variety of implant types.…”
Section: Introductionmentioning
confidence: 99%